'Abd al-Rahman b. 'Amr al-Awza'i - Judd, Steven C. (Simon and Schuster, 2019)
‘Abd al-Rahman b. ‘Amr al-Awza‘i (c.707–774) was Umayyad Syria’s most influential jurist, part of a generation of scholars who began establishing the first formal structures for the preservation and dissemination of religious knowledge. Following the Abbasid revolution, they provided a point of stability in otherwise unstable times. Despite his close ties to the old regime, al-Awza‘i continued to participate in legal and theological matters in the Abbasid era. Although his immediate impact would prove short-lived, his influence on aspects of Islamic law, particularly the laws of war, endures to this day.
Keywords: Biography & Autobiography / Historical; History / General; History / Middle East / General; Law / Islamic; Religion / History; Religion / Islam / General; Religion / Islam / Theology; Social Science / Islamic Studies; dept.his